2017
DOI: 10.1152/japplphysiol.00205.2017
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency blood pressure oscillations and inotrope treatment failure in premature infants

Abstract: The underlying mechanism as to why some hypotensive preterm infants do not respond to inotropic medications remains unclear. For these infants, we hypothesize that impaired vasomotor function is a significant factor and is manifested through a decrease in low-frequency blood pressure variability across regulatory components of vascular tone. Infants born ≤28 wk estimated gestational age underwent prospective recording of mean arterial blood pressure for 72 h after birth. After error correction, root-mean-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Total spectral power calculations were made in each of the four frequency bands (A-D) described in a previous publication. 23 Bands C (20-60 mHz) and D (60-160 mHz) were the strongest discriminators, with slightly better performance in band D (AUC ¼ 0.66, p ¼ 0.03). Slight modification of the frequency band limits to encompass regions of both bands C and D (25-65 mHz) resulted in significant improvement in model performance (AUC ¼ 0.73, p < 0.01).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Total spectral power calculations were made in each of the four frequency bands (A-D) described in a previous publication. 23 Bands C (20-60 mHz) and D (60-160 mHz) were the strongest discriminators, with slightly better performance in band D (AUC ¼ 0.66, p ¼ 0.03). Slight modification of the frequency band limits to encompass regions of both bands C and D (25-65 mHz) resulted in significant improvement in model performance (AUC ¼ 0.73, p < 0.01).…”
Section: Discussionmentioning
confidence: 92%
“…Using the same 3-hour time periods (18-21, 21-24, and 24-27 hours) as the time-series analysis, the total spectral power in four different candidate frequency bands was calculated using frequencies similar to those previously published by previous authors 23,24 and are listed in ►Supplementary Table S1 (available in the online version). As there were missing data introduced by the cleaning process, unequally spaced samples, the Lomb-Scargle method for spectral density estimation was used.…”
Section: Frequency-domain Analysismentioning
confidence: 99%
“…BP is known to be a slowly evolving signal ( Fig 3 ) and all important frequency components are within the 0–0.5 Hz band. Low frequency components of MAP were previously investigated for premature infants (0.005 Hz to 0.16 Hz) in [ 20 ] and adult population [ 21 ]. An example of a data segment is shown in Fig 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Currently, no treatment for IVH exists, though studies identifying risk factors and pathophysiology help to guide clinical care for prevention. One such study identified a strong association between improvements in blood pressure and increased in low-frequency variability in blood pressure within infants exposed to inotropes, often administered to improve mean arterial blood pressure (Vesoulis et al 2017). This variability was quantified using spectral analysis of certain low-frequency (0.005-0.16 Hz) components of the blood pressure signal and may be used as an adjunctive measure of response to these medications and potentially mitigating risk of hypertension-induced IVH (Bel et al 1987) through more optimal titration (Vesoulis et al 2017).…”
Section: Intraventricular Haemorrhagementioning
confidence: 99%